1989
DOI: 10.1128/aac.33.6.835
|View full text |Cite
|
Sign up to set email alerts
|

Suppression of colonic microflora by cefoperazone and evaluation of the drug as potential prophylaxis in bowel surgery

Abstract: We evaluated the activity of cefoperazone (CPZ) on the intestinal flora in terms of its use as a single prophylactic drug in colon surgery. Twenty-four healthy male volunteers between the ages of 20 and 40 were assigned to receive either CPZ, oral neomycin-erythromycin, or no antibiotics. A mechanical bowel preparation, Golytely, was also given to each of the subjects. With intravenous CPZ, antibiotic levels in the stool ranged from <2 to 649 ,ug/ml and the total fecal bacterial counts dropped 3 to 4 log1o CFU… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

1992
1992
2014
2014

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(2 citation statements)
references
References 19 publications
0
2
0
Order By: Relevance
“…Antibiotics with less anaerobic suppression (tetracycline, penicillin) appear to have a lower risk of CDAD. In one study, a cephalosporin given intravenously showed minimal anaerobic suppression; this increased when given orally [43].…”
Section: Antibiotics and The Fecal Floramentioning
confidence: 99%
“…Antibiotics with less anaerobic suppression (tetracycline, penicillin) appear to have a lower risk of CDAD. In one study, a cephalosporin given intravenously showed minimal anaerobic suppression; this increased when given orally [43].…”
Section: Antibiotics and The Fecal Floramentioning
confidence: 99%
“…Furthermore, it can be combined effectively with an oral antibiotic regimen given in the afternoon and evening before the planned operation the next morning. When given with the neomycin-erythromycin preparation, isotonic lavage achieves remarkable suppression of the aerobic and anaerobic flora; however, the lavage preparation alone, without antibiotics, fails to suppress the flora adequately [47].…”
Section: (Aj Scope Ofthe Guidelinementioning
confidence: 99%